(untitled) (PUBMET, 2023)
After twenty years of the open access movement, there has been growth in the uptake of open access, and some progress has been made in achieving its original goals; however, results have been far from satisfactory, with more than half of the research literature still closed (COKI, 2022; Curry, 2018). Moreover, new concerns have arisen, such as questionable quality and the reliability of peer review, in particular predatory publishing. There are also threats to equity, including stratifications of publishing as a consequence of the exclusionary character of the author-pays model of open access, and new risks of bias and exclusion in the means of transparent evaluation (Ross-Hellauer et al., 2022). It is argued that these challenges are the result of the uncritical narratives of openness and their narrow focus on access alone which fail to address inequitable power dynamics, systemic problems and the structural barriers in scholarly publishing and knowledge production (Perry, 2020; ibid.). These cha(lle)nges in the system of scholarly communication, coupled with recent advances in technology and the tectonic transformations in the information environment, require new (pedagogical) approaches and foci that would enable researchers and students to understand and navigate such a complex environment; for this, a holistic and integrative approach to scholarly communication and information literacy is needed (ACRL, 2013; Špiranec, 2015). Scholarly communication, including open access, is impossible without information literacy (Hebrang Grgić, 2016). As they are both concerned with (access to) information, open access and in particular critical information literacy largely share the same goals, ethical dimensions and values of (social and epistemic) justice, equity and democratisation. Indeed, they have been considered instrumental to achieving these, and even proclaimed a panacea and deus ex machina for the current scientific, social and political challenges and crises (Hebrang Grgić, 2016; Kapitzke, 2003). However, literature on the intersections and interplay between open access and information literacy has been limited. This paper seeks to intertwine these two concepts more strongly, for mutual exchange and benefit, by analysing their convergent aspects as well as the role information literacy has in the context of the complexities of the scholarly communication system and in achieving open access. The paper builds on the few empirical studies of the intersections between the two concepts (e.g. Hebrang Grgić (2016) which confirms the importance of ‘open access literacy’), but goes beyond their functional approaches, advocating a more holistic and critical approach to open access to help reinvent it and make a more substantial progress in open access. It argues that the transformations in the information environment and the scholarly communication system require not only basic skills and competences at the core of information literacy but also specific skills of, for instance, managing scientific data and publishing in open access sources. More importantly, what is also required is critical consciousness of all the aspects of the research process including the context, power relationships, and the privileged positions in knowledge production, publishing and dissemination, and an ability to evaluate the quality and reliability of information. The paper proposes critical open access literacy as a pedagogical methodology and strategy to confront the challenges and enable a critical understanding of the contemporary information environment and scholarly communication. In line with the tenets of critical information literacy, critical open access literacy is directed at an analysis and critique of the economic, social, political, legal and technological conditions, aspects and implications of open access and the overall scholarly communication system, as well as the power dynamics, tensions and flaws within them. This will empower students and researchers to navigate this environment successfully and potentially become champions of its transformation to make it more meaningful, reliable, equitable and democratic.